2016
DOI: 10.1002/pat.3893
|View full text |Cite
|
Sign up to set email alerts
|

Designing polymeric sensing materials: what are we doing wrong?

Abstract: Gas analytes, or volatile organic compounds, interact with polymeric sensing materials through various sensing mechanisms. The dominant sensing mechanisms are discussed for different types of volatile organic compounds, which are categorized by their functional groups. Based on these sensing mechanisms, a systematic approach is used to design and tailor polymeric sensing materials for specific analytes and applications. This approach also takes into consideration other constraints determined by the target appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 13 publications
(56 citation statements)
references
References 91 publications
2
54
0
Order By: Relevance
“…While this orientation of the carbon tetrafluoride-benzene complex agrees with the proposed sorption of benzene to SXFA, it has been shown that this orientation may not be explained by π-stacking, but rather charge transfer between the small molecules that reduces the electron density in the π-system [17]. A sensing mechanism was subsequently suggested in which benzene π-stacks onto one of the trifluoro-groups on SXFA, since the fluorine atoms form a planar ring (see Figure 2) [8]. This paper evaluates the proposed sensing mechanism between benzene and SXFA using a DFT approach.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…While this orientation of the carbon tetrafluoride-benzene complex agrees with the proposed sorption of benzene to SXFA, it has been shown that this orientation may not be explained by π-stacking, but rather charge transfer between the small molecules that reduces the electron density in the π-system [17]. A sensing mechanism was subsequently suggested in which benzene π-stacks onto one of the trifluoro-groups on SXFA, since the fluorine atoms form a planar ring (see Figure 2) [8]. This paper evaluates the proposed sensing mechanism between benzene and SXFA using a DFT approach.…”
Section: Introductionsupporting
confidence: 62%
“…To more efficiently design and tailor polymeric sensing materials for target analytes and specific applications, it is important to understand the sensing mechanisms by which analytes (and interferents) interact with sensing materials [8]. One way to investigate these sensing mechanisms is with Density Functional Theory (DFT) calculations [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This immediately reduces the amount of analyte molecules that are available to sorb. Also, as more gas analytes are simultaneously exposed to a sensing material, they compete for available sorption (sensing) sites . This often results in lower sorption of each gas analyte, which can be seen in Figures .…”
Section: Resultsmentioning
confidence: 99%
“…For example, such a sensor array could be one consisting of PoANI, poly (vinyl pyrrolidone) (PVP), poly (2,5‐dimethyl aniline) (P25DMA), and SXFA . These potential sensing materials were chosen because each one has acceptable partial selectivity to one of the four gas analytes evaluated in this paper; PoANI to acetone, PVP to ethanol, P25DMA to methanol, and SXFA to benzene.…”
Section: Resultsmentioning
confidence: 99%